4D printing of mashed potato/purple sweet potato puree with spontaneous color change. (January 2020) - He, Chang; Zhang, Min; Guo, Chaofan
Abstract: In this study, the effects of pH (2.5, 6.5 and 7.8) and potato flake content (15%, 19%, 23% and 27%) on the properties of mashed potatoes (MP) were studied in terms of moisture distribution, rheological properties, texture properties and 3D printing performances. Results showed that the potato flake content was positively correlated with apparent viscosity, storage modulus (G′), and loss modulus (G″), while negatively correlated with tanδ and relaxation time ( T 2 ). As the content of potato chips increased, the shape fidelity of MP increased after printing. The addition of citric acid increased MP's apparent viscosity, G′, hardness and gumminess, thus increasing its capacity to be self-supportable performance after deposition, while an opposite trend was observed when sodium bicarbonate was added. A dual-extrusion printer was furtherly used to manufacture a colorful 4D ready-to-eat food in terms of spontaneous color change by using anthocyanin-rich purple sweet potato puree and MP. Results indicated that the color change of MP was significantly correlated with the pH value and the potato flake content. Industrial relevance: This work extends the conventional 3D printing of single material to multi-material, and potentially provides a new view on how to produce colorful food products by 4D printing in terms of spontaneous color change of 3D printed multi-material products. Highlights: The effects of pH and potato flakes content on the 3D printing properties of mashed potatoes (MP) were studied. The effects of pH and potato flakes content on the spontaneous discoloration of dual-extrusion printed samples were studied. Results indicated that the color change of MP was significantly correlated with the pH and potato flakes content. The manufacture of three-dimensional ready-to-eat food with multi-material and multi-color was realized.